2021
DOI: 10.11628/ksppe.2021.24.1.17
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on the Perception of Companion Plants for Eco-Friendly Urban Agriculture among Urban Residents

Abstract: Background and objective: This study was conducted as part of research to promote garden diversity and seek sustainable garden management plans, as well as to determine the trends in understanding and use of companion plants as an eco-friendly farming method and provide the results as the basic data for sustainable urban agriculture. Methods: To determine the trends in garden activities, eco-friendly pest control, and use of companion plants, a survey was conducted on 230 urban residents participating in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Regarding gardening experience, 83 subjects responded that they are 'doing it now' (73.5%), followed by 'I' ve done it before, but not now' (16.8%) > 'never did' (8.0%) > others (1.8%) (Table 3). This result is consistent with the study by Hong et al (2021) reporting that 73.5% of respondents have gardening experience. Considering the increase in the area of urban agriculture and the number of participants every year, participation in urban agricultural activities will continue to grow.…”
Section: Demographic Characteristics Of Respondentssupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding gardening experience, 83 subjects responded that they are 'doing it now' (73.5%), followed by 'I' ve done it before, but not now' (16.8%) > 'never did' (8.0%) > others (1.8%) (Table 3). This result is consistent with the study by Hong et al (2021) reporting that 73.5% of respondents have gardening experience. Considering the increase in the area of urban agriculture and the number of participants every year, participation in urban agricultural activities will continue to grow.…”
Section: Demographic Characteristics Of Respondentssupporting
confidence: 93%
“…26 subjects responded that they interact by talking to one another (55.4%), followed by just greeting one another (21.7%) > only recognizing faces (12.0%) > meeting regularly (6.0%) > don't know (4.8%). 38 subjects (45.8%) responded that they share the harvested crops with family and neighbors, followed by sharing with family and friends (32.5%) > donating to local facilities or institutions (13.3%) > using at home (8.4%), showing similar results with studies by Hong et al (2021), Chae et al (2019),…”
Section: Survey On How To Use Garden Cropssupporting
confidence: 80%
“…Numerous attempts have been made to explore the physiological reactions of plants to activities like pot transfer or transplanting, which involve people actively participating in nature. This study demonstrated the value of urban farming as a complementary type of green space (Hong et al, 2021). Furthermore, it was anticipated that products from urban farming will affect human physiology during production and consumption (Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 71%
“…Companion plants are used for the purpose of blocking the inflow of pests or avoiding damage to establish an ecological pest control system for pests. As part of the push-pull farming method, the term is still unfamiliar in Korea (Cook et al, 2007;Finch and Collier, 2011;Parker et al, 2013), but the diverse terms used before such as companion plants, companion crops, and mixed food were unified and established as 'companion plants' in a relationship that helps one another or the other in the report by Hong et al (2020), after which the term has been more widely understood (Hong et al, 2021). Chrysanthemum farms effectively attracted thrips using eggplants as a trap plant (Kang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%